Tunable Metasurfaces Based on Active Materials - Cui, Tong; Bai, Benfeng; Sun, Hong‐Bo (Advanced functional materials, 2019)
Metasurfaces, planer artificial materials composed of subwavelength unit cells, have shown superior abilities to manipulate the wavefronts of electromagnetic waves. In the last few years, metasurfaces have been a burgeoning field of research, with a large variety of functional devices, including planar lenses, beam deflectors, polarization converters, and metaholograms, being demonstrated. Up to date, the majority of metasurfaces cannot be tuned postfabrication. Yet, the dynamic control of optical properties of metasurfaces is highly desirable for a plethora of applications including free space optical communications, holographic displays, and depth sensing. Recently, much effort has been made to exploit active materials, whose optical properties can be controlled under external stimuli, for the dynamic control of metasurfaces. The tunability enabled by active materials can be attributed to various mechanisms, including but not limited to thermo‐optic effects, free‐carrier effects, and phase transitions. This short review summarizes the recent progress on tunable metasurfaces based on various approaches and analyzes their respective advantages and challenges to be confronted with. A number of potential future directions are also discussed at the end. Various mechanisms to achieve dynamic control of metasurfaces enabled by active materials are discussed. Recent works on tunable metasurfaces based on thermo‐optic effects, free carrier effects, and phase transitions are summarized. Their respective advantages and challenges are analyzed and an outlook on the potential development of tunable metasurfaces is presented.